Unequal error correction strategy for magnetic recording systems with multi-track processing - L. M. M. Myint; P. Supnithi (My University, 2012)
In multi-track detection, the simultaneous recovery of user data of all tracks is obtained from multi-head or single-head reader with buffer. Due to incomplete inter-track interference (ITI) information of the outer tracks, unequal error rates exist among tracks. For a system with three-track processing, the center track exhibits a better performance than the others. In this work, we propose the unequal error protection (UEP) schemes to improve the overall system performance of a 2-D interference bit-patterned recording system with multi-track detection. The performances of the proposed schemes are investigated for the BPM channels with and without the media noise. Based on the simulation results, the proposed schemes offer the gain of about 0.2–0.3 dB over the equal error protection (EEP) scheme at a bit error rate of 10−4.
Keywords: Word error rate; Patterned media; Recording head; Cellular Automata and Applications